10.1 Can essential fatty acids prevent early preterm delivery? A meta-analysis of evidence. (9th June 2014) - Kar, S; Thangaratinam, S; Wong, M; Rogozinska, E
Abstract : Background: Amongst preterm babies, those delivered before 34 weeks gestations contribute disproportionately highly to prematurity related complications. There is a need for effective, acceptable, accessible and safe interventions to prevent early preterm delivery. Objective: To evaluate the effects of essential fatty acids on early (<34 weeks) and any (<37 weeks) preterm delivery and relevant fetal outcomes by a systematic review and meta-analysis. Methods: We searched MEDLINE, EMBASE and Cochrane Library (1970–2013). Randomised controlled trials that evaluated effects of essential fatty acids in preventing preterm delivery were selected. Results were summarised as relative risks and 95% confidence intervals for dichotomous outcomes and mean differences for continuous outcomes. We undertook subgroup analysis planned a priori according to the dose, timing of the intervention and risk status. Results: Of the nine randomised trials evaluating the effects of essential fatty acids on preterm delivery, six RCTs (4193 women) reported the effect on early preterm delivery. The risk of early preterm delivery was significantly reduced by 58% (RR 0.42, 95% CI 0.27, 0.66; p = 0.0002; I2 = 0%) with essential fatty acids compared to the control group. There was a 17% reduction in the overall risk of any preterm delivery (RR 0.83, 95% CI 0.70, 0.98; p = 0.03; I2 = 0%). Essential fatty acids significantly increased the mean gestational age by 2.0 weeks (95% CI 0.42, 3.5 weeks) and the mean birth weight by 122.1 g (95% CI 47.4, 196.8). Conclusion: Essential fatty acids prevent early preterm delivery.